Distinct Microbiota Composition and Fermentation Products Indicate Functional Compartmentalization in the Hindgut of a Marine Herbivorous Fish - Pardesi, B; Roberton, AM; Lee, KC; Angert, ER; Rosendale, DI; Boycheva, S; White, WL; Clements, KD (John Wiley & Sons, 2022)
Many marine herbivorous fishes harbour diverse microbial communities in the hindgut that can play important roles in host health and nutrition. Kyphosus sydneyanus is a temperate marine herbivorous fish that feeds predominantly on brown seaweeds. We employed 16S rRNA gene amplicon sequencing and gas chromatography to characterize microbial communities and their metabolites in different hindgut regions of six K. sydneyanus. Measurements were confined to three distal sections of the intestine, labelled III, IV and V from anterior to posterior. A total of 625 operational taxonomic units from 20 phyla and 123 genera were obtained. Bacteroidota, Firmicutes and Proteobacteria were the major phyla in mean relative abundance, which varied along the gut. Firmicutes (76%) was the most dominant group in section III, whereas Bacteroidota (69.3%) dominated section V. Total short-chain fatty acid (SCFA) concentration was highest in sections IV and V, confirming active fermentation in these two most distal sections. The abundance of Bacteroidota correlated with propionate concentration in section V, while Firmicutes positively correlated with formate in sections III and IV. Acetate levels were highest in sections IV and V, which correlated with abundance of Bacteroidota. Despite differences in gut microbial community composition, SCFA profiles were consistent between individual fish in the different hindgut regions of K. sydneyanus, although proportions of SCFAs differed among gut sections. These findings demonstrate functional compartmentalization of the hindgut microbial community, highlighting the need for regional sampling when interpreting overall microbiome function. These results support previous work suggesting that hindgut microbiota in marine herbivorous fish are important to nutrition in some host species by converting dietary carbohydrates into metabolically useful SCFAs.
Keywords: 16S rRNA; Algae; Digestion; Microbiota; Short-chain fatty acids